ASIAN DEVELOPMENT BANK LOAN FOR KERALA : THE ADVERSE IMPLICATIONS AND SEARCH FOR ALTERNATIVES - Ravi Raman, K (Centre for Development Studies-WP357, 2004)
The privileging of internal resources over external finance is not only the most democratic but also the most politically desirable option. The implications of the ADB loan for Kerala is situated against this premise by employing an empirical political economy method. The paper is divided into five sections. In section 1, along with the structure of the loan, the current status of state finance is briefly outlined. Section 11 explores two hypotheses: the Resource Mobilisation Crisis Hypothesis and the Debt Overhang Hypothesis. In section 111, the socio-political implications of the ADB loan are discussed in the context of the conditionalities imposed. In section IV, viable alternatives are analysed with special emphasis on internal resource mobilisation and section V summarises observations. It is pointed out that the debt sustainability in Kerala was foreclosed by the late 90s with the state is in debt overhang. The ADB loan would only be an attack on the fiscal health of the state. Moreover, the class bias of the state blinds it to encrypted sources of funds which in Kerala help foster social structures of accumulation, leading to what could be called a state-`augmented/patronised' fiscal crisis. If theKerala government were to adhere to ADB-driven governance, it would culminate in social de-investment, "commodification" of critical sectors such as education and health and thereby a reversion of whatever remains of the Kerala model of social development; vulnerable social sections being the hardest hit. Although the state has accepted the first tranche, it could just as well withdraw totally from the ADB package. What is required is a concerted effort towards an internal resource mobilisation which would liberate the state from its commitment to the high-conditionality ADB loan. A mere 20 per cent or less of the locked up funds/arrears would save the state from seeking the second tranche. The state would be well advised to first stop further borrowing from the ADB and to dispense with theADB policy package, and, second, to renounce the path of externallydriven neo-liberal reforms.